Аналіз успадкування деяких кількісних ознак гороху посівного - Мамалига, В.С.; Кондратенко, М.І.; Бугайов, В.Д.; Янчук, В.І. (Фактори експериментальної еволюції організмів, 2013)
Aims. The character of inheritance of plants height, quantity of beans on a plant, bulk of seeds per plant and quantity of seeds per one bean in the F1 hybrids of pea was researched. Methods. 5 different varieties of pea were crossed under the accredited method and indications of hybrids productivity in comparison with parents forms were analyzed. Results. It is determined that the inheritance of researched characteristics is controlling by aditive and dominant system of genes with predominating both additive and nonaditive genes, that gives the opportunity to recommend the selection of perspective plants in early generations. Conclusions. Researched varieties of pea are valuable sources of high productivity characteristics in their use in the selection programs for creation of new high productive varieties suitable to growing under modern intensive technologies.